Towards an international language for incontinence‐associated dermatitis (IAD): design and evaluation of psychometric properties of the Ghent Global IAD Categorization Tool (GLOBIAD) in 30 countries. (1st June 2018) - Beeckman, D.; Van den Bussche, K.; Alves, P.; Arnold Long, M.C.; Beele, H.; Ciprandi, G.; Coyer, F.; de Groot, T.; De Meyer, D.; Deschepper, E.; Dunk, A.M.; Fourie, A.; et al.
Summary: Background: Incontinence‐associated dermatitis (IAD) is a specific type of irritant contact dermatitis with different severity levels. An internationally accepted instrument to assess the severity of IAD in adults, with established diagnostic accuracy, agreement and reliability, is needed to support clinical practice and research. Objectives: To design the Ghent Global IAD Categorization Tool (GLOBIAD) and evaluate its psychometric properties. Methods: The design was based on expert consultation using a three‐round Delphi procedure with 34 experts from 13 countries. The instrument was tested using IAD photographs, which reflected different severity levels, in a sample of 823 healthcare professionals from 30 countries. Measures for diagnostic accuracy (sensitivity and specificity), agreement, interrater reliability (multirater Fleiss kappa) and intrarater reliability (Cohen's kappa) were assessed. Results: The GLOBIAD consists of two categories based on the presence of persistent redness (category 1) and skin loss (category 2), both of which are subdivided based on the presence of clinical signs of infection. The agreement for differentiating between category 1 and category 2 was 0·86 [95% confidence interval (CI) 0·86–0·87], with a sensitivity of 90% and a specificity of 84%. The overall agreement was 0·55 (95% CI 0·55–0·56). The Fleiss kappa for differentiating between category 1 and category 2 was 0·65 (95% CI 0·65–0·65). The overall Fleiss kappa was 0·41 (95% CI 0·41–0·41). The Cohen's kappa for differentiating between category 1 and category 2 was 0·76 (95% CI 0·75–0·77). The overall Cohen's kappa was 0·61 (95% CI 0·59–0·62). Conclusions: The development of the GLOBIAD is a major step towards a better systematic assessment of IAD in clinical practice and research worldwide. However, further validation is needed.